Caring for Psychological Distress of Patients With COVID-19: A Mixed-Method Cross-Sectional Study - Li, Juan; Wang, Anni; Liu, Lei; Chen, Xue; Bai, Xiaoling (Frontiers in Psychology, 2022)
Introduction: The 2019–2020 pandemic COVID-19 has become a global health crisis. While many recent studies on COVID-19 pandemic have focused on disease epidemiology and the psychological status of patients, few have explored the multi-facet influential factors or combined perspectives from both the patients and healthcare workers. The purposes of this study were to: analyze the influencing factors of psychological distress of COVID-19 patients; and describe the experience of healthcare workers relieving psychological distress. Materials and Methods: This study uses a mixed-method cross-sectional design, including a quantitative study and a qualitative study, targeting two populations: COVID-19 patient and health workers, respectively. In the quantitative part, we recruited a convenience sample of patients with COVID-19 from five hospitals in Wuhan, Hubei Province from 10 April to 15 April, 2020. Besides, we collected data by using participants’ socio-demographic information sheet, the Connor-Davidson Resilience Scale-10, the Herth Hope Index, the Distress Thermometer, the Revised Chinese Version of Mishel Uncertainty in Illness Scale, and the Chinese Version of Wake Forest Physician Trust Scale. In the qualitative part, the participants were healthcare workers involved in medical aid missions in Hubei Province, China. Meanwhile, we used sampling with convenient and purposive, data collection with a semi-structured online video interview, and text transcription with Colaizzi's phenomenological method. Results: The results reveal that 25.7% of patients reported a higher level of psychological distress (n=31, scoring≥4). After controlling the sociodemographic variables, only the severity of COVID-19 (β=0.282, P=0.025) and uncertainty in illness (β=0.345, P=0.007) shown significant effect on psychological distress in the regression model (F=10.862, R2=0.222, P<0.001). The experience of healthcare workers emerged five themes: Particularly needed psychological care, Manifestation of negative emotion, Manifestation of proactive adaptation, Strategies relieving psychological distress, and gains of healthcare workers after delivering effective psychological care. Conclusions: The 25.7% of patients with COVID-19 still suffered from psychological distress, which should receive timely attention from healthcare workers. And the severity of the disease and disease uncertainty has a significant impact on distress. It is critical to train the healthcare workers on detecting the different manifestations of psychological distress, offering timely disease-related information, and applying communication strategies.